Radio frequency analog-to-digital converters: Systems and circuits review. (January 2022) - Li, Dengquan; Zhao, Xin; Liu, Shubin; Liu, Maliang; Ding, Ruixue; Liang, Yuhua; Zhu, Zhangming
Abstract: With emerging demands of wideband radios and wireless communication, radio frequency (RF) analog-to-digital converters (ADCs) are greatly required. In recent years, the advance in technology allows a rapid development of RF ADCs, especially boosting various hybrid architectures and backend digital signal processing circuitry. This paper reviews and discusses recent advances on the design topologies of RF ADCs, including several innovative architectures and techniques. Comparison between different techniques on bandwidth, power, and noise could provide the designers a broad perspective to meet their requirements.